Pengaruh Kualitas Pelayanan, Fasilitas dan Harga Terhadap Kepuasan Konsumen - Fairurrissa Wijayanti; Basar Maringan Hutauruk (Journal of Trends Economics and Accounting Research, 2023)
The economy in Indonesia has developed in a better direction. This can be seen by the rapid development of the business world, where more and more business actors open and develop their businesses. One of the growing businesses in Indonesia is the culinary business. Many similar businesses have sprung up resulting in stronger competition, therefore business people must be able and quick and responsive in making good decisions so that the business they establish can develop. This research uses quantitative methods. The method used in the quantitative research approach. The research method is utilized in sample studies and certain populations, where data acquisition is carried out using research instruments and data analysis which has statistical/quantitative properties with the aim of testing predetermined hypotheses. This quantitative research approach is used by researchers to measure the influence between brand ambassadors, brand image, product quality and purchase decisions. The results of several analyses that have been said state the conclusion that partially service quality has a significant effect on customer satisfaction, facilities affect customer satisfaction, price has a significant effect on customer satisfaction. The results of the analysis of service quality, facilities and prices simultaneously affect customer satisfaction.